The materiality of texts from ancient Egypt: new approaches to the study of textual material from the early pharaonic to the late antique period - Hoogendijk, F. A. J.; Gompel, Steffie M.T. van (Papyrologica Lugduno-Batava, 2018)
Front Matter -- Copyright page -- Preface /Francisca Hoogendijk and Steffie van Gompel -- Notes on Contributors -- Figures -- Abbreviated Literature -- Editorial Notation -- The Material Authority of Written Texts in Pharaonic Egypt /Christopher Eyre -- The Platypus Paradox: An Archaeological Approach to Ancient Egyptian Writing Practices /Massimiliano S. Pinarello -- Telling Them by Their Hands: What Palaeography Has to Offer Prosopography /Rodney Ast -- The Body of the King and of the Goddess: Materiality in and through Manuals for Pharaoh from Tebtunis /Susanne Töpfer -- Material Matters: Documentary Papyri and Ostraca in Late Ramesside Thebes /Ben Haring -- Writing on Ostraca: Considerations of Material Aspects /Julia Lougovaya -- Ceramic Supports and Their Relation to Texts in Two Groups of Ostraca from the Fayum /Clementina Caputo and James M.S. Cowey -- Evolving Epigraphic Standards in the Field: Documenting Late Period and Graeco-Roman Egyptian Graffiti through Photogrammetry at Elkab /Luigi Prada and Paul D. Wordsworth -- Revealing the Material World of Ancient Writing: Digital Techniques and Theoretical Considerations /Kathryn E. Piquette -- Back Matter -- Bibliography.